In vivo model for mastocytosis: A comparative review. Issue 3 (March 2015) - Ranieri, Girolamo; Marech, Ilaria; Pantaleo, Marianna; Piccinno, Mariagrazia; Roncetti, Maria; Mutinati, Maddalena; Rizzo, Annalisa; Gadaleta, Cosmo Damiano; Introna, Marcello; Patruno, Rosa; Sciorsci, Raffaele Luigi
Highlights In vivo models of mast cell tumors (CMCTs) could represent a valid model to study human mastocytosis. We have focused on human mastocytosis in terms of: (i) epidemiology and classification; (ii) pathogenesis at molecular levels; (iii) clinical presentation. We have summarized animal models useful to study neoplastic MC disorders. We have revised therapeutic approaches mostly common in human and canine MCTs and novel tyrosine kinase inhibitors approved for CMCTs and translated in human clinical trials.